2019
DOI: 10.1055/s-0038-1676953
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adjuvant Homeopathy with Usual Care in Management of Thrombocytopenia Due to Dengue: A Comparative Cohort Study

Abstract: Background Dengue is an emerging threat to public health. At present, no clear modalities are available for the prevention and management of thrombocytopenia due to dengue. This article reports the clinical outcomes of integrative homeopathic care in a hospital setting during a severe outbreak of dengue in New Delhi, India, during the period September to December 2015. Methods Based on preference, 138 patients received a homeopathic medicine along with usual care (H+UC), and 145 patients received u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…In the dengue haemorrhagic fever study, add-on homoeopathy could bring early improvement in increasing platelet count and curtailing the in-hospital stay by 2 days. 26 In acute encephalitis syndrome/Japanese encephalitis study, homeopathy as an adjuvant to the institutional management protocol could decrease death rate by 15% in comparison to those who received only institutional management protocol. 27 Notably in both the studies, no adverse effects were found.…”
Section: Homoeopathic Treatment For Epidemicsmentioning
confidence: 97%
“…In the dengue haemorrhagic fever study, add-on homoeopathy could bring early improvement in increasing platelet count and curtailing the in-hospital stay by 2 days. 26 In acute encephalitis syndrome/Japanese encephalitis study, homeopathy as an adjuvant to the institutional management protocol could decrease death rate by 15% in comparison to those who received only institutional management protocol. 27 Notably in both the studies, no adverse effects were found.…”
Section: Homoeopathic Treatment For Epidemicsmentioning
confidence: 97%
“…An Indian comparative observational study on thrombocytopenia due to dengue fever, conducted at an allopathic hospital set-up, resulted in better results of adjuvant homeopathy compared with usual care alone in increasing the platelet counts. 37 Another Indian comparative study on patients with acute encephalitis syndrome showed reduction in mortality and morbidity in the group administered adjuvant homeopathy to standard institutional management protocols compared with standard therapy alone. 38 Another method to minimize confounding and bias before starting a study (at baseline) is to control using a matching technique.…”
Section: Comparative Cohort Studiesmentioning
confidence: 99%
“…8 In India, such patient-centred approaches to studying the impact of homeopathy in public healthcare are already being performed on a large scale, often in resource-limited situations. Dr Debadatta Nayak showed how individualised homeopathy can play a role in the management of thrombocytopenia (low blood platelet count) associated with Dengue, alongside conventional care 9 ; Dr Raj Manchanda presented encouraging positive results from a trial of homeopathy, used as an adjunct to conventional medicine, in the treatment of encephalitis in children 10 ; and Dr Anil Khurana presented the results of a public health initiative involving use of a six-remedy kit to promote healthy development in the teething stage in 11,426 children. 11…”
Section: Public Health and Patient Interestsmentioning
confidence: 99%